The effect of genetic variation and nitrogen fertilization on productive characters of Greek oregano. (19th May 2017) - Ninou, Elissavet G.; Paschalidis, Konstantinos A.; Mylonas, Ioannis G.; Vasilikiotis, Christos; Mavromatis, Athanasios G.
ABSTRACT: This study aims to investigate the response of 10 Greek Oregano ( Origanum vulgare subsp. hirtum ) populations, collected across Greece, under 3 levels of N-fertilization during 2012 and 2013. The populations were differentiated for dry matter (from 32.7 to 63.3 g·pot −1 ), for essential oil content (from 2.31 to 5.86 ml·100 −1  g dry weight) and for amount of essential oil (from 1.37 to 2.46 ml·pot −1 ), for both years. Those with the highest dry matter (1-"Palaiochori" and 5-"Gliki") and the highest essential oil content (10-"Gytheio" and 9-"Achladocastro") were superior by 30%, as compared to the general mean of the experiment. The populations 3-"Litochoro" and 5-"Gliki" had an increased amount of essential oil (24%) as compared to the general mean of the experiment. An additional nitrogen supply (N0 to N1 level) increased dry matter production and amount of essential oil per pot, while decreased essential oil content for all populations. Further increase of nitrogen supply, favored six populations for dry matter production and two populations for amount of essential oil per pot while had almost no effect on five populations for essential oil content. The superior populations could be used in a breeding program as starting material for the development of new cultivars.